Pengaruh Fundamental Makro, Kinerja Keuangan, Struktur Kepemilikan, Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan : Studi Pada Perusahaan BUMN Diindonesia Yang Terdaftar Pada Bursa Efek Indonesia - Indhira Ridho Abdhilla; Hwihanus Hwihanus (Universitas 45 Surabaya, 2023)
The aim of this research is to explore and assess the impact of Macro Fundamentals, Financial Performance, Ownership Structure, and Company Growth on the valuation of state-owned companies that are publicly listed on the Indonesia Stock Exchange between 2020 and 2022. The research employs a quantitative descriptive approach, utilizing secondary data from both independent and dependent variables. The data is sourced from financial statements, annual reports, and various online platforms, including the Indonesia Stock Exchange website (www.idx.co.id). The study encompasses all state-owned companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022, with a 15-company sample selected through random sampling. The results of hypothesis testing reveal that one independent variable significantly influences the dependent variable, while eight variables show insignificant effects on company value.